Анализ особенностей состояния высокотемпературных роторов и факторов, влияющих на их работоспособность и ресурс - Пугачева, Татьяна Николаевна (НТУ "ХПИ", 2009)
The issues has been treated connected of determination of residual resource of service of high temperature knots of turbine. Factors determining duration of reliable exploitation of turbine are analysed: exhausting of the protracted plasticity from the creep of material; accumulation of damages in the critical areas of rotors because of a cyclical fatigue.
Keywords: тепломеханическое оборудование; электростанции; высокотемпературные узлы; длительная пластичность